Individualism and stock price crash risk - An, Zhe; Chen, Zhian; Li, Donghui; Xing, Lu (Journal of International Business Studies, 2018)
Employing a sample of 26,473 firms across 42 countries from 1990 to 2013, we find that firms located in countries with higher individualism have higher stock price crash risk. Furthermore, individualism can be transmitted by foreign investors from overseas markets to influence local firms’ crash risk, and can exacerbate the impact of firm risk taking and earnings management on crash risk. Moreover, the positive relation between individualism and crash risk is amplified during the global financial crisis and attenuated by enhanced country-level financial information transparency and the adoption of International Financial Reporting Standards.